2013
DOI: 10.1111/dme.12198
|View full text |Cite
|
Sign up to set email alerts
|

Associations between pigment epithelium‐derived factor, insulin resistance and high density lipoprotein

Abstract: Serum pigment epithelium-derived factor is positively associated with homeostasis model assessment-insulin resistance and negatively associated with HDL. Further studies are needed to understand the mechanism of low HDL and raised pigment epithelium-derived factor and to determine if they are causally related to the pathobiology of insulin resistance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…In vitro data have shown that an increased dosage of HDL reduced the secretion of PEDF in adipocytes. However, the mechanisms of regulating PEDF expression and secretion by HDL is not clarified yet [ 29 ]. A previous study showed that the administration of D-4F, an apolipoprotein A1 mimetic peptide might markedly attenuate the oxLDL-provoked decrease in PEDF protein and messenger ribonucleic acid (mRNA) expression in human umbilical vein endothelial cells [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…In vitro data have shown that an increased dosage of HDL reduced the secretion of PEDF in adipocytes. However, the mechanisms of regulating PEDF expression and secretion by HDL is not clarified yet [ 29 ]. A previous study showed that the administration of D-4F, an apolipoprotein A1 mimetic peptide might markedly attenuate the oxLDL-provoked decrease in PEDF protein and messenger ribonucleic acid (mRNA) expression in human umbilical vein endothelial cells [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Many researchers have reported the positive correlation between PEDF and cardiometabolic risk factors, such as waist-to-hip ratio, waist circumference, homeostasis model of assessment of insulin resistance (HOMA), TG, and reduced HDL-C levels in patients with obesity, MetS or T2D (Yamagishi et al 2018). In patients with impaired fasting glucose or T2D, PEDF concentrations were associated with HOMA, BMI, and decreased HDL-C, and after niacin therapy, HDL-C levels were an independent determinant of PEDF in these patients (Pek et al 2013). Furthermore, waist circumference, TG, creatinine, and tumor necrosis factor-α (TNF-α) were independently correlated with PEDF in T2D patients (Nakamura et al 2009).…”
Section: Discussionmentioning
confidence: 99%